Cost-benefit analysis and ideas for cost sharing of groundwater irrigation: evidence from north-eastern Ethiopia - Gebregziabher, Gebrehaweria; Villholth, Karen G.; Hanjra, Munir A.; Yirga, M.; Namara, R. E. (2023)
The government of Ethiopia has invested in groundwater development for smallholder irrigation in the Raya Valley and Kobo Valley, north-eastern Ethiopia, where the hydrogeological potential is large but not fully developed. A cost-benefit analysis shows that investment in deep groundwater irrigation development is viable at a 9.5% discount rate in 75% of the wells. Assuming full cost recovery of capital investment, the annual payment rates (annuity) that irrigation users should pay over the wells’ service life (25 years) were estimated. It is recommended that future investment be based on cost sharing rather than full cost recovery to facilitate uptake and address financial realities.